Prolonged screen-time as the cause of ocular disorders: what can we do with the problem? – a review - Dyrek, Martyna; Sikorska, Ewa; Partyka, Aleksandra; Sikorski, Piotr; Dusza, Edyta; Kopacz, Dorota (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Recently, an increased use of video display terminals has been observed in workplace environments, as a result of the evolution of communication technologies and new information-sharing strategies. It has led to an increased prevalence of computer-related ocular disorders, such as computer vision syndrome, dry eye disease, refractive errors and con vergence insufficiency. In this review we describe problems associated with these disorders and propose preventive methods. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. With the use of specific keywords, the databases of the PubMed, Science Direct, and Google Scholar were searched for relevant original papers. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literature. The listed disorders might have similar symptoms, such as eye burning, itching, blurred vision, and tearing, and their severity correlates with the time of exposure to video display units. However, there are preventive measures, which can help in decreasing the negative effects of computers on our vision, such as adequate viewing distance, proper work space lighting, eyeglasses with anti-glare coating, taking 5-minutes breaks after every 30 minutes, or following the 20-20-20 rule. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Prolonged usage of the video display terminals is connected to many ocular disorders, and in today’s world, it is very important to remember actions that can be undertaken to minimize the risk.